Strategy Improves Ability To Know Hijaiyah Letters Through Picture Card Media In Children Aged 5-6 Years - Wardani, Lestiyana (Universitas Muhammadiyah Ponorogo, 2023)
This research aimed to ascertain the efforts of teachers in increasing the recognition of hijaiyah letters in early childhood. The type of research used was descriptive qualitative. The place of study was at RA Bakti 16, Gemah Ngargoyoso Karanganyar Village. Collecting data was carried out through observation, interviews, and documentation. The strategy carried out by the teacher in increasing the knowledge of hijaiyah letters used picture card media, namely by telling stories and with exciting games. This strategy has been carried out well so that with this media, it is easier for children to recognize hijaiyah letters as the key to reading the Qur'an